Uso de plantas con propiedades medicinales en la comunidad del cantón Yacuambi durante el período Julio-Diciembre 2011 - Ramírez Ruiz, Carlos Jair (2014)
In order to establish the frequency of use of medicinal plants of the people living in the canton Yacuambi to know the signs and symptoms that motivate their use and how to gain knowledge about the same, a descriptive study was planned, prospective with quantitative and cross design approach whose sample includes 201 individuals, which were given a survey. Obtaining as results: 100% of respondents use medicinal plants, residing in the parish 28 May (59.20%) are ethnic Saraguro (74.10%), with incomplete primary education level (44, 8%), over 50 (37.31%), female (87.56%) are farmers (37.31%). Medicinal plants used to treat signs and symptoms: stomach pain (89.55%), infection, nerve, air and coughing. Knowledge about the use of plants with medicinal properties they obtain indications of family and community tradition. The use of plants with medicinal properties is part of ancestral knowledge that are held by family tradition, which they use to treat various ailments naturally.